2011
DOI: 10.1183/09031936.00099811
|View full text |Cite
|
Sign up to set email alerts
|

RSV infection modulates IL-15 production and MICA levels in respiratory epithelial cells

Abstract: The cytokine interleukin (IL)-15, major histocompatibility complex (MHC) class I molecules and MHC class I chain-related proteins (MIC) A and B are involved in cellular immune responses to virus infections but their role in respiratory syncytial virus (RSV) infection has not been studied. We aimed to determine how RSV infection modulates IL-15 production, MHC class I and MICA expression in respiratory epithelial cells, the molecular pathways implicated in virusinduced IL-15 production and how interferon (IFN)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 33 publications
0
43
1
Order By: Relevance
“…It is known that the ciliated epithelium secretes a number of anti-viral and anti-microbial agents, including defensins and antimicrobial peptides. In our study, the level of the anti-viral cytokine interferon-c was three-fold higher in the ciliated cell system compared with the basal cell system, and this may reduce viral yield through the activation of host transcription factors [22]. However, there are limitations in directly comparing these two culture systems.…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of mentioning
confidence: 84%
“…It is known that the ciliated epithelium secretes a number of anti-viral and anti-microbial agents, including defensins and antimicrobial peptides. In our study, the level of the anti-viral cytokine interferon-c was three-fold higher in the ciliated cell system compared with the basal cell system, and this may reduce viral yield through the activation of host transcription factors [22]. However, there are limitations in directly comparing these two culture systems.…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of mentioning
confidence: 84%
“…Furthermore, the expression of IL-15 is induced in DCs upon LPS or IFN-γ stimulation and is elevated in epithelial cells by infection (7,8). Transcription factors such as NF-κB and IFN regulatory factor 1 (IRF-1) reportedly function in its expression (9)(10)(11).…”
mentioning
confidence: 99%
“…It has been revealed that deficits of IL-15 in asthmatic patients result from an impaired response to Rhinovirus infection in vitro, which possible indicates that the cytokine has a protective effect against such infections (22). The respiratory syncytial virus was found to contribute to the upregulation of IL-15 in a study on bronchial and alveolar epithelial cell lines (43). Moreover, there is evidence that IL-15 is a significant factor responsible for the production of CD8 + memory T cells in response to viral infection (44).…”
Section: Discussionmentioning
confidence: 98%